ChemInform Abstract: Black Arsenic—Phosphorus: Layered Anisotropic Infrared Semiconductors with Highly Tunable Compositions and Properties. Issue 41 (October 2015) - Zhou, Chongwu; et al.
Abstract Black AsxP1‐x (x = 0, 0.25, 0, 4) is prepared by vapor transport of a mixture of gray As and red P to which a Sn/SnCl4 mixture is given as mineralizer (evacuated silica tubes, complex heating and cooling schedules) and subsequently exfoliated for optical and electrochemical measurements.